PENDAPAT AL-MAZÂHIB AL-ARBA’AH TENTANG BENTUK SYIRKAH DAN APLIKASINYA DALAM PERSEROAN MODERN - Susamto, Burhanuddin (Fakultas Syariah, 2014)
The practice of sharia principles in our life is a necessity. A corporation as a part of life is not out of the frame of sharia perspective. The desire to view the corporation from the sharia perspective is starting from the fact that in fiqh muamalah there are some relevant contract, especially syirkah contract. Al-mazâhib al-arba'ah through their books of fiqh have introduced the similarities and differences of opinion concerning shirkah forms which original law is allowed according to the Qur'an, the Sunnah and ijma '. Therefore, through this article, the author will reveal again the opinion of the each schools concerning syirkah forms and how to implement it in the context of a modern corporation.